The Influence of Digital Marketing, Price and Product Quality on Buying Decision in MSMEs (Culinary Sector) in Medan City - Sopang, Fandi Iskandar; Marviana, Ratna Dina (Ekonomis: Journal of Economics and Business, 2025)
The purpose of this study is to determine the influence of digital marketing, price, and product quality on purchasing decisions in fostered MSMEs in Medan City. The population in this study was all fostered MSMEs in Medan City, totaling 1,875; then using purposive sampling so that the number of samples used was 213. Hypothesis testing was carried out by analyzing the structural model, namely using Structural Equation Modeling (SEM). The results of this study concluded that digital marketing and product quality variables have a significant effect on purchasing decisions. However, the price variable does not affect purchasing decisions in MSMEs (Culinary Sector) in Medan City.